BUILDING A DIGITAL-BASED (POST-PANDEMIC) MODERATE MUSLIM URBAN COMMUNITY: REFLECTION ON THE INTERPRETATION OF DA’WAH VERSES - Azizy, Jauhar; Sihabussalam, Sihabussalam; Desmaliza, Desmaliza (AKADEMIKA: Jurnal Pemikiran Islam, 2022)
Extremism is a common problem requiring resolution by various parties. One of the causes of extremism is the paradigm of primordialism and ethnocentrism, which asserts the superiority of individuals or groups and tends to demean others. In addition, socio-religious changes due to the Covid-19 pandemic also have intensified the situation of a pluralistic Indonesian society and have even permeated through cyberspace. Therefore, this study aimed to reflect on the interpretation of the verses calling for a response to the post-Covid-19 condition of Muslim urban communities. This study also aimed at maintaining the harmony of Indonesian society, specifically urban Muslims, while reinforcing a moderate attitude after the outbreak. A qualitative method was adopted using content analysis. The result showed that the reflection of these da'wah verses led to the importance of digital da'wah as a means of building (post-pandemic) moderate urban Muslim communities by upholding the goals of Islam, namely rahmatan li al-‘alamin, and collective benefit. Six ways were identified in building a moderate, digital-based Muslim urban community. First, through media literacy and digital literacy, second, a preacher must have the courage to expose potential, third, grounding the content of moderation on social media, and fourth, forming a group of moderate-minded digital media account managers. The fifth is strengthening collaboration with influencers (people who are influential in social media) and the sixth is courteous communication.